The Effect of Compensation and Work Environment on Work Ethos That Impact on Employee Performance at PT. Mitraindo Perkasa in Jakarta - Dian Rostikawati; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of compensation and work environment on work ethic which has an impact on employee performance at PT. Mitraindo Perkasa in Jakarta. The method used is explanatory research with a sample of 125 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study Compensation has a significant effect on work ethic by 26.7%, hypothesis testing obtained a significance of 0.000 <0.05. Work environment has a significant effect on work ethic by 41.5%, hypothesis testing obtained a significance of 0.000 <0.05. Compensation and work environment simultaneously have a significant effect on work ethic by 47.2%, hypothesis testing obtained a significance of 0.000 < 0.05. Work ethic has a significant effect on employee performance by 39.1%, hypothesis testing is obtained a significance of 0.000 < 0.05.